KEBIJAKAN PERSEDIAAN SUKU CADANG DI PT ABC MENGGUNAKAN METODE RCS (RELIABILITY CENTERED SPARES) - Fransiskus Tatas Dwi Atmaji; Anak Agung Ngurah (Politeknik APP Jakarta, 2018)
Based on data from the production and maintenance department, the highest downtime happen in JDK machine at ABC company. High downtime caused by spare parts lacking or replacement parts when the machine damaged, it cause the engine stop longer. This study analyze and determine spare part inventory the policy, especially critical components in JDK machine. Reliability Centered Spare (RCS) method used in this study, this method essentially determines the optimal spare parts policy for a certain period. The result of research with RCS method shows that the spare parts inventory policy for all critical components of JDK machine in one year ahead by storing or stocking the following amount: packing valve: 469 pieces; teflon: 134 pieces; bearing pump: 10 pieces; mechanical seal: 26 pieces; motor pump: 10 pieces; packing pump: 141 pieces; motor driving reel: 9 pieces; bearing driving reel: 45 pieces; mechanical seal driving reel: 163 pieces; packing heat exchanger: 70 pieces; site glass: 29 pieces; and pressure gauge: 7 pieces.